TAXONOMIC KEYS FOR SPECIES OF Heliothis (LEPIDOPTERA: NOCTUIDAE) IN COLOMBIA - HALLMAN, GUY (Revista Colombiana de Entomología, 1978)
Taxonomic keys for large larvae and adults of the species of Heliothis known to exist in Colombia, H. virescens( Fabricius), H. zea (Boddie), H. tergeminus (Felder & Rogenhofer), and H subflexus(Guenée), are presented. Spodoptera frugiperda (J.E. Smith) is included in the larvae key because it is often confused with Heliothis spp, in this growth stage. Another, unknown species of Heliothis collected from cotton is also included in the larvae key. Methods of distinguishing sex in the pupa) and adult stages are also given.